Sosialisasi Kajian Teknis terhadap Pengembangan Aplikasi LMS Inklusi Digital untuk Pengguna Difabel - Syifaurachman Syifaurachman; Muhamad Ihsan Ashari (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Inclusive digital learning platforms offer a strategic solution to bridge the educational access gap for persons with disabilities in Indonesia. This community service initiative was conducted at the Paradifa Indonesia Foundation, which acts as a facilitator for the use of web-based Learning Management Systems (LMS) designed for users with disabilities. The project aimed to combine user needs analysis with a comprehensive technical review to support the development of an inclusive LMS. The activities involved seminars and technical briefings as part of a structured socialization process. Topics included enterprise architecture, system components, LMS design layers, cloud-based system structures, and technical evaluations. The findings support the recommendation to adopt a microservices-based enterprise architecture hosted in the cloud, addressing key factors such as server performance, data protection, interoperability, and accessibility for disabled users.This program is expected to strengthen both development and facilitation teams in implementing inclusive digital learning solutions. Additionally, it ensures that the system architecture and security mechanisms are reliable and adaptive to user needs. The outcomes may serve as a replicable model for other institutions aiming to develop accessible and efficient LMS platforms for inclusive education in Indonesia.